Pushing Daddy Away? A Qualitative Study of Maternal Gatekeeping - Hauser, Orlee (Qualitative Sociology Review, 2012)
There is a great deal of literature regarding the differences between motherhood and fatherhood. The literature suggests that parenthood is deeply gendered and takes on different meanings for men and for women. This paper examines parenthood from an angle not typically addressed in feminist discussion. Missing from recent scholarship is any in-depth examination of the role that women may play in limiting the involvement of their male partners. What part do women play in the maintenance of traditional parenting roles? This paper, based on a series of interviews with parents of young children as well as field research in child centered locations, concentrates on the reasons behind the emergence of gendered parenting approaches. The qualitative nature of this study makes it possible to note the complexity of this issue and examine the role of both mother and father in gatekeeping. Overall, I argue that many mothers are involved in maternal gatekeeping through taking control over both major and minor parenting decisions, through controlling access to parenting information and through implementing control mechanisms during their absence. I discuss the means by which some mothers attempt to limit their partners’ involvement and the ambivalence that this creates for both parents involved.